2017
DOI: 10.1158/0008-5472.can-17-1589
|View full text |Cite
|
Sign up to set email alerts
|

PHGDH as a Key Enzyme for Serine Biosynthesis in HIF2α-Targeting Therapy for Renal Cell Carcinoma

Abstract: Continuous activation of hypoxia-inducible factor (HIF) is important for progression of renal cell carcinoma (RCC) and acquired resistance to anti-angiogenic multi-kinase and mTOR inhibitors. Recently, HIF2α antagonists PT2385 and PT2399 were developed and are being evaluated in a Phase I clinical trial for advanced or metastatic clear cell RCC (ccRCC). However, resistance to HIF2α antagonists would be expected to develop. In this study, we identified signals activated by HIF2α deficiency as candidate mediator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 31 publications
0
66
1
Order By: Relevance
“…Disturbing PHGDH by siRNA or NCT-503, an inhibitor of PHGDH, the tumoricidal effect was improved and sensitivity to erlotinib was restored in cell lines and xenografts [90,91]. Additionally, suppression of PHGDH can eradicate advanced or metastatic clear cell renal cell carcinoma (ccRCC) resistant to HIF2α antagonists by inducing apoptosis [92]. PHGDH knocked down with RNAi and knocked out by CRISPR/Cas9 or inactivated by inhibitor can overcome tyrosine kinase inhibitor (TKI) drug resistance, including sorafenib, regorafenib, or lenvatinib, in hepatocellular carcinoma (HCC) [93].…”
Section: Phgdh and Tumor Resistance To Chemotherapy Drugsmentioning
confidence: 99%
“…Disturbing PHGDH by siRNA or NCT-503, an inhibitor of PHGDH, the tumoricidal effect was improved and sensitivity to erlotinib was restored in cell lines and xenografts [90,91]. Additionally, suppression of PHGDH can eradicate advanced or metastatic clear cell renal cell carcinoma (ccRCC) resistant to HIF2α antagonists by inducing apoptosis [92]. PHGDH knocked down with RNAi and knocked out by CRISPR/Cas9 or inactivated by inhibitor can overcome tyrosine kinase inhibitor (TKI) drug resistance, including sorafenib, regorafenib, or lenvatinib, in hepatocellular carcinoma (HCC) [93].…”
Section: Phgdh and Tumor Resistance To Chemotherapy Drugsmentioning
confidence: 99%
“…However, sunitinib therapy does not have curative effects due to RCC’s acquisition of resistance 4 . Moreover, our previous study showed the occurrence of metabolic re‐programming in RCC cells, leading to sunitinib resistance 5 . In November 2015, anti–programmed death‐1 (PD‐1) antibodies were approved for the treatment of patients with sunitinib‐resistant RCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, sunitinib therapy is not expected to have curative effects because it extends progression-free survival only slightly due to acquisition of resistance to sunitinib [ 4 ]. Moreover, metabolism re-programming was observed in RCC cell that showed sunitinib resistance to evade undesirable environment in our previous study [ 5 ]. Recently, anti-programmed death-1 (PD-1) antibodies were approved for the treatment of patients with advanced ccRCC.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, in this study, we aimed to investigate the anti-cancer efficiency of JQ1 in vitro and in vivo and to elucidate the molecular mechanisms underlying BRD4 inhibition in sunitinib-sensitive and -resistant ccRCC. First, we investigated the anti-cancer effects of JQ1 in vitro and in vivo using ccRCC cell lines, including sunitinib-resistant 786-o (SU-R-786-o), which we had previously established in vivo [ 5 ]. To identify key molecules in sunitinib-resistant ccRCC cells treated with JQ1, we performed RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%